Elevation Changes of West-Central Greenland Glaciers From 1985 to 2012 From Remote Sensing - Huber, Jacqueline; McNabb, Robert; Zemp, Michael (Frontiers in Earth Science, 2020)
Greenlandic glaciers distinct from the Ice Sheet make up 12% of the global glacierized area and store about 10% of the global glacier ice volume (Farinotti et al., 2019). However, knowledge about recent climate change-induce volume changes of these 12,000 individual glaciers is limited. The small number of available glaciological and geodetic mass-balance observations have a limited spatial coverage, and the representativeness of these measurements for the region is largely unknown, factors which make a regional assessment of mass balance challenging. Here we use two recently released digital elevation models (DEMs) to assess glacier-wide elevation changes of 1,526 glaciers covering 3,785 km 2 in west-central Greenland: The historical AeroDEM representing the surface in 1985 and a TanDEM-X composite representing 2010-2014. We show that on average glacier surfaces lowered by about 14 ± 4.6 m from 1985 until 2012 or 0.5 ± 0.2 m per year, which is equivalent to a sample mass loss of approximately 45.1 ± 14.9 Gt in total or 1.7 ± 0.6 Gt per year. Challenges arise from the nature of the DEMs such as large areas of data voids, fuzzy acquisition dates, and potential radar penetration. Data voids and unknown survey dates are addressed by comparing and evaluating different interpolation methods resulting in a best guess estimation and a related uncertainty analysis. The potential radar penetration is considered negligible for this assessment in view of the overall glacier changes and the length of the observation period. A comparison with earlier studies indicates that for glacier change assessments based on ICESat, data selection and averaging methodology strongly influences the results from these spatially limited measurements. This study promotes improved assessments of the contribution of glaciers to sea-level rise and encourages to extend geodetic glacier mass balances to all glaciers on Greenland.